Advances in parasitology. Volume 38 - Baker, John R. (John Robin); Muller, Ralph, 1933-; Rollinson, D. ([Place of publication not identified] : Academic Press, 1996)
Advances in Parasitology is a series of up-to-date reviews of all areas of interest in contemporary parasitology. It includes medical studies on parasites of major influence, such as typanosomiasis and scabies, and more traditional areas, such as zoology, taxonomy, and life history, which shape current thinking and applications.
Includes index.
Online resource; title from publisher's Web site (ScienceDirect, viewed on June 4, 2012).
Elsevier
Keywords: Parasitology; Parasitology; Electronic books